Achievement Evaluation of IFI Assistance Loans to China (1981-2002) - Hu, Angang; Hu, Guangyu (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Loans from international financial institutions (IFI loans) to China were a very important beginning to China's opening to the outside world. This book represents the first comprehensive study done in China to evaluate the overall performance of IFI assistance to China from 1981 to 2002. It analyzes the efficiency of international assistance in contributing to the Chinese economy by investigating the actual implementation of the projects and their economic, financial, social, ecological, and educational impacts. It draws on successful cooperations between the Chinese government and IFIs, analyzes major lessons in project management, and provides recommendations on how to further develop international cooperations that are mutually beneficial. Angang Hu is the director of the Center for China Studies and a professor at the School of Public Policy and Management, Tsinghua University. His research work is noticed by Chinese leadership, and often influences government policies.